After the Unesco Delors Report: professionalism and skills of the teacher in European school - Mulé, Paolina (Formazione & insegnamento, 2017)
In this work, 21 years after the publication of the Delors Report, the A. analyzes one of the pillars of education: learning to know, bearing in mind that the teacher must have disciplinary skills, education sciences, technical-professional, socio-relational, general teaching and disciplinary teaching, to generate in future generations the acquisition, updating and use of knowledge. From the study emerge several issues present both in the Italian and international landscape about the existence of a gap between pedagogy and didactics which, although two disciplines are scientifically founded with their own theoretical and methodological implications, are often very little known by curriculum professors. Hence, the urgency of elaborating an epistemological reflection on the training of the subject, questioning the models and processes of teaching and training, of in-service training that appear ,today, quite different from the past, both in Italy and in Europe.